Comparison of sandstone mechanic properties using acoustic test and direct uniaxial test - Samsuri, Ariffin (2004)
Rock mechanic characterization usually can be done through direct test, with uniaxial or triaxial test by equipment of compression unit. The velocity of ultrasonic wave with compressional (P) wave and shear (S) wave can determine the value of rock mechanic characteristic such as Poisson Ratio and Young Modulus. In this study the two test method used for sand stone sample is taken from outcrop. If the result obtained from uniaxial direct test is assumed approximately true value, then the determination of correction factor from acoustic test can be performed to get a equation. By knowing the correction factor of a rock taken from a specific location, one can determine rock mechanic characteristics obtained from the same location without destructing the rock due to testing.